2018
DOI: 10.4168/aair.2018.10.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E-binding Proteins of Cooked Walnuts in Korean Children

Abstract: PurposeThe immunological characteristics of young Korean children with walnut (WN) allergy and the influence of different cooking methods on WN proteins have not been evaluated to date. This study aimed to evaluate the major WN allergens identified among Korean children, together with changes in WN antigenicity caused by common cooking methods.MethodsWe enrolled children under the age of 13 years with WN serum-specific immunoglobulin (Ig) E concentrations. The protein fractions of dry-fried and boiled WN extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The present study on this issue focused on identifying the usual methods of cooking walnuts in order to investigate changes in walnut allergen activity caused by cooking and evaluated the allergenic changes in walnut proteins within raw, dry-fried and boiled walnuts. 17 In addition, the effects of different cooking methods showed that of the 66 proteins, 57 were found in untreated walnuts with dry-fried walnuts and only 4 were seen in boiled walnuts. Interestingly, the remaining allergenic components of cooked walnuts cause serious reactions when consumed by children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study on this issue focused on identifying the usual methods of cooking walnuts in order to investigate changes in walnut allergen activity caused by cooking and evaluated the allergenic changes in walnut proteins within raw, dry-fried and boiled walnuts. 17 In addition, the effects of different cooking methods showed that of the 66 proteins, 57 were found in untreated walnuts with dry-fried walnuts and only 4 were seen in boiled walnuts. Interestingly, the remaining allergenic components of cooked walnuts cause serious reactions when consumed by children.…”
mentioning
confidence: 99%
“…A few studies have looked for combinations of processing methods to alter the allergenicity of foods. 17 18 However, there are different views with regard to walnut allergy. Some treatments, such as dry-roasting can reduce IgE-binding capacity in vitro .…”
mentioning
confidence: 99%